Implementasi Metode FUCOM-SAW Pada SPK Pemilihan di Indonesia - Gede Surya Mahendra (Tech-E, 2021)
Blibli, Bukalapak, JD.id, Lazada Indonesia, Shopee and Tokopedia are designated as the 6 largest e-commerce in Indonesia based on the 2019 Consumer Pulse eIQ. The increase in e-commerce transactions has greatly impacted the positive growth of e-commerce. The positive growth in e-commerce in Indonesia has resulted in Indonesia being predicted to become the market leader in Southeast Asia. E-commerce customers have personal preferences in choosing e-commerce for transactions. Various criteria make customers confused because of the intense competition between e-commerce companies. DSS is a solution in choosing the right e-commerce for each customer's preferences. The FUCOM-SAW method can be used in calculations to determine favorite e-commerce in Indonesia. The CRISP-DM framework also helps in preparing the research flow well. 4 decision makers were used to assign weighting criteria using FUCOM. The results of this study indicate that the Bukalapak alternative is the best e-commerce, with a preference value of 0.8701. The second and third place respectively are Blibli and Tokopedia. The weighting of the criteria by decision makers, the alternative normalization process and the technique of calculating preference values ​​have a significant effect on the ranking results.